Altered phagocytic capacity due to acute exposure and long-term post-exposure to pesticides used for vector-borne disease as dengue. Issue 2 (1st February 2022) - Girón-Pérez, D. A.; Hermosillo-Escobedo, A. T.; Macias-Garrigos, K.; Díaz-Resendiz, K. J. G.; Toledo-Ibarra, G. A.; Ventura-Ramón, G. H; Girón-Pérez, M. I.
ABSTRACT: Spinosad and temefos are widely used pesticides for chemical control of dengue vector-borne disease ( Aedes aegypti ). The aim of this study was to compare the effect of acute exposure (7 days) to spinosad (0.5 mg A.I. L −1 ) and temefos (10 mg A.I. L −1 ), concentrations used by the Mexican Ministry of Health, on phagocytic capacity (PC) of mononuclear cells of guppies fish ( Poecilia reticulata ), as well as to assess PC in fish, at 96 days after exposure to those pesticides. Obtained results indicated that spinosad did not alter PC, while an acute exposure to temefos significantly affected phagocytosis and this parameter was maintained downed even 96 days after the acute exposure, suggesting that the immunotoxic effects of temefos may be chronic.